Changing Health Care Systems from Ethical, Economic, and Cross Cultural Perspectives - Loewy, Erich H.; Loewy, Roberta Springer (Springer Netherlands, 2002)
This volume is the result of a conference sponsored by the Medical Alumni Association of the University of California, Davis and held in Sacramento, California, in January, 2000, The purpose of this conference was to examine the impact ofvarious health care structures on the ability of health care professionals to practice in an ethically acceptable manner. One of the ground assumptions made is that ethical practice in medicine and its related fields is difficult in a setting that pays only lip service to ethical principles. The limits of ethical possibility are created by the system within which health care professionals must practice. When, for example, ethical practice necessitates—as it generally does—that health care professionals spend sufficient time to come to know and understand their patients’ goals and values but the system mandates that only a short time be spent with each patient, ethical practice is made virtually impossible. One of our chief frustrations in teaching health care ethics at medical colleges is that we essentially teach students to do something they are most likely to find impossible to do: that is, get to know and appreciate their patients’ goals and values. There are other ways in which systems alter ethical possibilities. In a system in which patients have a different physician outside the hospital than they will inside, ethical problems have a different shape than if the treating physician is the same person